SHEVCHENKO STUDIES OF IVAN FRANKO IN THE RECEPTION OF YURI BOIKO-BLOKHIN - Khiminets, A. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates Yuri Boiko-Blokhin’s reception of Ivan Franko views on the work of Taras Shevchenko, the ideological and aesthetic features and poetical poetry of Shevchenko. It is demonstrated how Boyko-Blokhin analyzes in details the changes in these attitudes in the methodological and contextual perspective.